The Swedish model for prioritising research on the use of antibiotics: Aligning public funding with research gaps. Issue 8 (August 2022) - Skoog Ståhlgren, Gunilla; Grape, Malin; Edlund, Charlotta
Highlights: Improved use of antibiotics, aims to reduce resistance pressure, side effects and societal costs. Public sector can play a fundamental role in identifying clinical important knowledge gaps. Antibiotic stewardship requires regular revisions of guidelines based on solid scientific data. An independent reference group and predefined criteria were key in the model. Coordinated national and international efforts are essential for successful implementation in healthcare. Abstract: Due to the meagre development of new antibiotics, optimising the use of currently available antibiotics is important to reduce resistance pressures and to safeguard existing treatment options. The Public Health Agency of Sweden (PHAS) was tasked in 2014 to (1) develop a model for identifying and prioritising research gaps and (2) initiate studies to improve knowledge on how to optimise the use of existing antibiotics. A survey addressing knowledge-gaps and suggesting studies needed was distributed to a broad network of Swedish and European clinicians and experts. An independent reference group prioritised the proposals, applying predefined criteria focusing on public health relevance. The PHAS sponsored and led two multi-centre RCTs in cooperation with clinical researchers and took part in additional studies. A second survey and prioritization exercise following the same model was performed in 2019. The Swedish case study described in this paper provides an example of the role that the public sector can play in order to support the improved use of existing antibiotics. National and international institutions are well suited to perform systematic reviews of research priorities with a focus on public health concerns. The ultimate success of the model depends on political engagement, a close dialogue with healthcare professionals, collaboration between international sister-authorities responsible for public health in other countries, the availability of research funding, harmonisation of regulatory issues and regular revisions of clinical guidelines. The experience from the Swedish model illustrates opportunities for meeting clinical needs and filling knowledge gaps on existing off-patent antibiotics.